Intra-articular injection, subacromial injection, and hydrodilatation for primary frozen shoulder: a randomized clinical trial - Yoon, Jong Pil; Chung, Seok Won; Kim, Ju-Eun; Kim, Hyung Sup; Lee, Hyun-Joo; Jeong, Won-Ju; Oh, Kyung-Soo; Lee, Dong-Oh; Seo, Anna; Kim, Youngjun (MOSBY-ELSEVIER, 2016)
Background: The aim of this prospective randomized study was to compare the efficacy of 3 injection methods, intra-articular injection, subacromial injection, and hydrodilatation (HD), in the treatment of primary frozen shoulder. Methods: Patients with primary frozen shoulder were randomized to undergo intra-articular injection (n = 29), subacromial injection (n = 29), or HD (n = 28). Evaluations using a visual analog scale for pain, Simple Shoulder Test, Constant score, and passive range of shoulder motion were completed before treatment and 1 month, 3 months, and 6 months after treatment. Results: Among the 3 injection methods for primary frozen shoulder, HD resulted in a greater range of motion in forward flexion and external rotation, a lower visual analog scale score for pain after 1 month, and better outcomes for all functional scores after 1 month and 3 months of follow-up. However, there were no significant differences in any clinical outcomes among the 3 groups in the final follow-up at 6 months. Conclusions: Although HD yielded more rapid improvement, the 3 injection methods for primary frozen shoulder resulted in similar clinical improvement in the final follow-up at 6 months. (C) 2016 Journal of Shoulder and Elbow Surgery Board of Trustees
Keywords: ROTATOR CUFF REPAIR; IDIOPATHIC ADHESIVE CAPSULITIS; CORTICOSTEROID INJECTIONS; ARTHROSCOPIC RELEASE; DIABETES-MELLITUS; JOINT DISTENSION; PHYSIOTHERAPY; MANIPULATION; ARTHROGRAPHY; MANAGEMENT